Clinical and immunological features of patients with atopy and concomitant HTLV-1 infection - Gaspar-Sobrinho,F.P. (2010)
Human T-cell lymphotropic virus type 1 (HTLV-1) induces an exacerbated type 1 immune response characterized by high spontaneous IFN-γ and TNF-α production. Allergic rhinitis and asthma are associated with the type 2 immune response, with elevated secretion of IL-4 and IL-5. The aim of this study was to characterize the immune response in atopic HTLV-1 carriers. The cytokine profile of atopic HTLV-1 carriers (N = 10; all females) was compared with that of non-atopic HTLV-1 carriers (N = 14; 9 females and 5 males). Mean patient age of atopic and non-atopic groups was 45 ± 8 and 38 ± 11 years, respectively. All atopic HTLV-1 carriers had rhinitis with or without asthma and a skin prick test positive for Dermatophagoides pteronyssinus antigen 1 (Derp-1). There was no difference in cytokine levels between the two groups in unstimulated peripheral blood mononuclear cell cultures. In cultures stimulated with Derp-1, IFN-γ levels tended to be higher (P = 0.06) and IL-5 levels were higher (P = 0.02) in atopic HTLV-1 patients than in non-atopic subjects. In contrast, IL-10 was lower (P = 0.004) in atopic than in non-atopic HTLV-1-infected subjects. This study shows that HTLV-1 infection with an exaggerated type 1 immune response does not prevent atopy. In this case, the exacerbated type 1 and type 2 immune responses were due to a lack of IL-10 production, a cytokine that plays an important role in down-modulating type 1 and type 2 immune responses and in preventing the development of chronic inflammatory diseases.